2016
DOI: 10.1007/jhep04(2016)024
|View full text |Cite
|
Sign up to set email alerts
|

Scalar dark matter in scale invariant standard model

Abstract: Abstract:We investigate single and two-component scalar dark matter scenarios in classically scale invariant standard model which is free of the hierarchy problem in the Higgs sector. We show that despite the very restricted space of parameters imposed by the scale invariance symmetry, both single and two-component scalar dark matter models overcome the direct and indirect constraints provided by the Planck/WMAP observational data and the LUX/Xenon100 experiment. We comment also on the radiative mass correctio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…The H 2 field (scalon) is massless, and it can be shown that the elastic scattering cross section of DM off nuclei becomes drastically large and the model is immediately excluded by the direct detection experiments. The one-loop correction gives a mass to the massless eigenstate H 2 [2], [6]:…”
Section: The Modelmentioning
confidence: 99%
“…The H 2 field (scalon) is massless, and it can be shown that the elastic scattering cross section of DM off nuclei becomes drastically large and the model is immediately excluded by the direct detection experiments. The one-loop correction gives a mass to the massless eigenstate H 2 [2], [6]:…”
Section: The Modelmentioning
confidence: 99%
“…Scale-invariant extensions of the SM can also provide a DM candidate (for recent papers see e.g. [70][71][72][73][74][75][76][77][78][79][80]). Particle nature of the DM is another important puzzle in particle cosmology [81].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism works only if extra bosonic degrees of freedom are added to SM with sizable couplings. Scale-invariant extensions of SM are also a generic feature of many DM models with bosonic [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and fermionic [20][21][22][23][24][25][26] DM candidates.…”
Section: Introductionmentioning
confidence: 99%